Early Administration of Therapeutic Anticoagulation Following Intravenous Thrombolysis for Acute Cardiogenic Embolic Stroke Caused by Left Ventricular Thrombus: Case Report and Topic Review - Gill, Rick; Donahey, Elisabeth; Ruland, Sean (Frontiers in Neurology, 2015)
Cardiogenic cerebral embolism represents 20% of all acute ischemic strokes (AISs) with one-third of these being caused by left ventricular thrombus (LVT). LVT is not a contraindication for treatment with intravenous recombinant tissue plasminogen activator (IV rtPA) for AIS. However, the subsequent treatment of a potentially unstable LVT is contraindicated for 24 h following the use of IV rtPA according to current guidelines. We present a 66-year-old man with AIS treated with IV rtPA. Echocardiogram shortly after treatment demonstrated both a large apical and septal thrombus in the left ventricle and at 12 h post IV rtPA infusion, therapeutic anticoagulation with heparin was started without complication. In practice, the action of IV rtPA outlasts its apparent half-life because of thrombin-binding and the prolonged effects and longer half-life of its product, plasmin; however, the pharmacokinetics do not warrant prolonged avoidance of therapeutic anticoagulation when clinically indicated. Our case demonstrates that anticoagulation for potentially unstable LVT can be safely initiated at 12 h following IV rtPA treatment for AIS.